Meningkatkan Literasi Investasi Syariah Pada Pelajar Smk Nusantara Tangerang Selatan - Candra, Hendra; Fahri, Fahri; Kohar, Abdul (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
Sharia investment is a form of financial management that is in accordance with Islamic principles, which not only pays attention to financial benefits but also considers ethical and moral aspects. This research aims to provide understanding to students of SMK Nusantara Tangerang Selatan regarding sharia investment and can also be a recommendation for educational institutions in integrating Islamic financial education into their curriculum. This study uses a qualitative approach with a case study method with an exploratory descriptive research design. The population of this study is all students of SMK Nusantara in South Tangerang and the sampling is done using the purposive sampling technique. The analysis technique uses thematic analysis techniques with the analysis process starting with the transcription of the results of interviews and observations, followed by a coding process to identify the main themes that emerge from the data. The results of the study show that students of SMK Nusantara in South Tangerang have a fairly good understanding of the basic concept of sharia investment and in general, students show a very positive attitude towards sharia investment. They believe that sharia investment is safer and in accordance with religious values. Students who receive support and guidance from teachers and families show a better understanding of sharia investment